The Influence Of Learning Media (Pocket Book &Video Diabetes Manajemen) To Knowledge Level Of Diabetes Manajemen And Blood Glucose Level Of Diabetes Patients' - Sudiarto Sudiarto; Supriyadi Supriyadi; Heru Supriyatno (Pusat Penelitian dan Pengabdian kepada Masyarakat, Poltekkes Kemenkes Semarang, 2012)
The aim of this study was to explore the effect of pocket book and video diabetic management toward knowledge and compliance level of diabetic management and blood glucose level. Design that employed was quasy ekperimental with non equivalen control group and was conducted in the time series. There were 38 respondents distributed into two groups, one of each consist of 19 respondents. Based on the Wilcoxon statistical test, the results showed that there was a significant different in the post test 2 both in the video group group (p= 0,004) and pocket book group (p= 0.001), in the knowledge level and diabetic management (video p=0.010, pocket book p= 0.005). However, there was not significant different in the blood glucose level for the both groups ( p 0.05). Based on the result, it is recommended that implementation of intervention both for video and pocket book diabetic management should be underwent periodically ino 7 days maximally, therefore the expected goals can be gained.